Is rheumatoid arthritis always preceded by a symptomatic at-risk phase of arthralgia? - Hanna W van Steenbergen; Annette H M van der Helm-van Mil; Sarah J H Khidir; Anna M P Boeren; Stijn Claassen (RMD Open)
Objectives Secondary prevention of rheumatoid arthritis (RA) is generally considered potentially impactful because the entire RA population is believed to experience a symptomatic ‘pre-RA’ phase. We wondered whether this dogma is correct. Therefore we investigated an inception cohort of patients with newly diagnosed RA and studied among them patients who did and did not present with preceding arthralgia at risk for RA.Methods Consecutively diagnosed patients with RA between 2012 and 2022 were studied (n=699). These patients had either directly presented with clinically apparent arthritis, or had first presented with clinically suspect arthralgia (CSA). Clinical characteristics at symptom onset and RA diagnosis were compared. Whether certain characteristics frequently occurred together was studied using a K-means algorithm after dimension reduction with partial least squares discriminant analysis. To validate that groups differed in long-term outcomes, sustained disease-modifying anti-rheumatic drug-free remission (SDFR) of the groups was studied during a median follow-up of 5.3 years.Results Patients with RA who had first presented with CSA were younger, more often had a gradual symptom onset and were more often anti-citrullinated protein antibodies (ACPA)-positive. Studying characteristics at symptom onset and RA diagnosis revealed four patient clusters, of which two clusters included almost all patients with a preceding CSA phase. Patients in these two clusters (55% of RA population) were younger, had a gradual symptom onset, longer symptom duration and were more frequently ACPA-positive. Patients with RA in these clusters achieved SDFR less often (HR 0.51 (95% CI 0.37 to 0.68)) than the patients with RA in the two clusters where preceding CSA was infrequent/absent.Conclusion These data suggest the notion that the entire RA population has an identifiable symptomatic risk stage should be refuted. This may impact on the scope of preventive interventions targeting the symptomatic risk phase.